The Effect of the Number of Work Shifts for Erection Box Girder Using Launching Gantry on the Cost and Implementation Time in the Medan-Binjai II Railway Line Project - Mulyati, Ely; Amelia, Dessy (BANDAR: JOURNAL OF CIVIL ENGINEERING, 2025)
Resource management strategies in the construction sector play a vital role in achieving cost efficiency and accelerating project execution time. One applicable form of resource management is the implementation of shift work management. In the context of a railway overpass construction project utilizing the erection box girder method with a Launching Gantry and experiencing delays, the configuration of shift schedules becomes a critical variable due to its direct impact on operational costs and project duration. This study was conducted by developing a work schedule for the erection of box girders using Microsoft Project software for two shift work scenarios: a single-shift system and a two-shift system. Subsequent analysis was carried out to evaluate the project duration and calculate the implementation costs for each shift alternative.The analysis results indicate that the implementation of a two-shift work system has a significant impact on time efficiency and cost control. By adopting a two-shift system, the project duration can be accelerated by up to 48 days compared to a single-shift system. In terms of cost, the two-shift system is also able to reduce total project implementation costs by approximately 3.5% compared to the single-shift alternative.